ETHICAL LEADERSHIP, LEADER-FOLLOWER RELATIONSHIP AND PERFORMANCE: A STUDY IN A TELECOMMUNICATIONS COMPANY - NIEMEYER,JEANE RODRIGUES LUCENA (2016)
ABSTRACT Purpose: Analyze the influence of ethical leadership on the relationship between leaders and followers, as well as its consequences for individual performance, commitment to work goals, and organizational citizenship. Originality/gap/relevance/implications: Although ethics in leadership is supposed to promote positive consequences in the work context, its association with performance and other relevant aspects in the business environment - such as the commitment to goals - has not yet been empirically studied. The present research contributes by filling this gap, therefore expanding the knowledge about the implications of ethical leadership in Brazil. Key methodological aspects: A survey was conducted in a multinational telecommunications company, with a sample of 161 store clerks and 15 managers responsible for the sales units located in the city of Rio de Janeiro. The statistical analysis was done using the software SPSS, through multiple regression analyses conducted with the variables studied. Summary of key results: The results corroborate the benefits of ethical leadership. They show a positive association between ethical leadership and both the quality of the leader-follower relationships and employee performance. Key considerations/conclusions: The research suggests that ethical leadership seems to have a positive impact on work productivity, by building a better relationship with employees. Therefore, based on the findings, it is possible to recommend specific actions in leadership development programs, calling attention to the importance of discussing ethical dilemmas, behaviors, and models of practice.